Korea : a very short introduction - Seth, Michael J., 1948- (Oxford : Oxford University Press, 2020)
Having spent centuries in the shadows of its neighbours China and Japan, Korea is now the object of considerable interest for radically different reasons - the South as an economic success story and for its vibrant popular culture; the North as the home to one of the world's most repressive regimes, at once both bizarre and menacing. This book explores the history, culture, and society of a deeply divided region. Michael Seth considers what it means to be Korean, and analyses how the various peoples of the Korean peninsula became one of the world's most homogeneous nations, before exploring how this nation evolved, in a single lifetime, into today's sharply contrasting societies. He also discusses how Korea fits into the larger narrative of both East Asian and world history, economically, politically, and socially.
Also issued in print: 2020.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed on January 27, 2020).
Keywords: Korea; Korea -- History